Livelihood Change as Impact of Rural-Urban Transformation in Sleman Regency - Benino Indra Ardhityatama (Jurnal Wilayah dan Lingkungan, 2014)
Indonesia as one of many developing countries in the world is facing the same problem, which is about the rapidly high level of urbanization. In Indonesia, this transformation from rural to urban area will give impact to the changing of current livelihood, especially to the area that depends on the agriculture sector. Looking at more specific area, Yogyakarta is one of the big provinces in Indonesia that has rural and urban characteristic. The research question is “How does the rural community still resilient on agriculture based condition towards urbanization related to the livelihood changes?” This research focuses on the discovery on what family condition that they still resilient for their agriculture livelihood even though there are many changes caused by the urbanization. Qualitative method is used in this study because it can describe how people feel and their thoughts deeply, but it cannot tell you how many of the target population feel or think that way as quantitative method can. The study area development in Sleman and Godean Sub-District is triggered by the existence of the main access or main road. People that live alongside the main access are more likely to not become farmer again, so does to people that live in collector road. However, those who live in the remote area where the level of urbanization is low, the livelihood there is likely still as farmer considering the agriculture land still can be found easily. The general conclusion of this research is that the farmers in Sleman and Godean Sub-District have considerably high adaptability level. This is shown by the ability of the farmer that still can find a way to survive from the rapid urbanization that reduced their work field availability.